Uptake and Translocation of Cesium in Lettuce (Lactuca sativa L.) under Hydroponic Conditions - Leiping Shi; Longmiao Yuan; Ruijie Li; Wei Wang; Zhe Ding; Jianjun Liang; Junli Qiu; Ping Li (Adsorption Science & Technology)
The uptake of radiocesium (RCs) by plants is key to the assessment of its environmental risk. However, the transfer process of RCs in the water-vegetable system still remains unclear. In this work, the uptake and accumulation processes of Cs+ (0-10 mM) in lettuce were explored under different conditions by using hydroponics. The results showed that the higher exposure concentration of Cs+ could lead to a faster uptake rate and would be beneficial to the uptake and accumulation of Cs+. The uptake of K+ by roots and leaves was inhibited significantly when Cs+ concentration increased, but unapparent for Ca2+ and Mg2+. It was found that the higher K+ and Ca2+ concentration was, the higher inhibition was found for the uptake of Cs+ in root. The uptake of Cs+ leads the decrease of chlorophyll content and brought a negative effect on plant photosynthesis, consequently, a negative effect on lettuce morphology and obvious decrease of biomass and root length. The contents of glutathione (GSH), malondialdehyde (MDA), and root vitality were increasing during the growth following stress of high concentrations of Cs+, which caused stresses on the antioxidant system of lettuce. The enrichment coefficient for Cs+ in leaves was in the range of 8-217. Moreover, the transfer factor was in the range of 0.114-0.828, which suggested that the high Cs+ concentration could enhance the transfer of Cs+ from lettuce root to leaf. This study provides more information on the transfer of RCs from water to food chain, promoting the understanding of the potential risk of RCs.